Harmoni Sosial Keagamaan Masyarakat Hindu dan Muslim di Desa Jati Bali - Aulia, Guruh Ryan; Nisa, Isna Khairun (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
Abstract; The Religious Social Harmony of Hindu and Muslim communities in Jati Bali Village show that The social-religious harmony, being peaceful and respectful to each other, while the perceptions of Muslims show that there are no differences in understanding in various differences in terms of ethnicity, race and religion. Supporting factors build and strengthen the foundations of harmony and place love in the lives of religious people. The inhibiting factors are today’s challenges, the establishment of houses of worship, and interfaith marriages that are not approved by their parents. the local government is able to maintain the harmony that has existed in the village. Preferably in the village it is necessary to increase the learning of youth in order to build a tolerance system. Interfaith marriages should be carried out with the consent of both parties so that there are no disagreements. To be approved for the construction of a house of worship, the local community must obtain approval from the government. Keywords; Social Harmony; Hindu; Muslim